Demographic modeling via 3-dimensional Markov chains - Víquez, Juan José (2018)
This article presents a new model for demographic simulation which can be used to forecast and estimate the number of people in pension funds (contributors and retirees) as well as workers in a public institution. Furthermore, the model introduces opportunities to quantify the financial flows coming from future populations such as salaries, contributions, salary supplements, employer contribution to savings/pensions, among others. The implementation of this probabilistic model will be of great value in the actuarial toolbox, increasing the reliability of the estimations as well as allowing deeper demographic and financial analysis given the reach of the model. We build a mathematical and probabilistic model that allows us to capture the singularities of the transitions between states with enough flexibility that it can be applied to several scenarios. We successfully estimate its first moments, and show how to adjust the required probabilities. In order to verify the exactness of the proposed model we applied it to real data from a public institution, showing that the estimation error is below the 2%.